Aktionsart and multiple events in the selkup dialects; XLinguae; Vol. 9, iss. 4 - Bolsunovskaya L. M. Ludmila Mihailovna; Abramova R. N. Raisa Nikolaevna; Pozdeeva G. P. Galina Petrovna; Korotchenko T. V. Tatiana Valerievna (2016, 2016)
Title screen